1998
DOI: 10.1046/j.1464-410x.1998.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing transurethral microwave thermotherapy: a model for studying power, blood flow, temperature variations and tissue destruction

Abstract: Objective To examine the role of microwave power andResults Treatment monitoring and consistency were better during feedback TUMT than fixed-energy TUMT, blood flow on temperature variations and tissue destruction in the prostate, using a theoretical model in that the former compensated for variations in blood flow rate. The modelled values agreed with obserof transurethral microwave thermotherapy (TUMT), and thus compare fixed-energy TUMT with no intravations during real TUMT. Conclusions Blood flow rate is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…4,5,9 Furthermore, "treatment energy," which is commonly used to describe the intensity of TUMT, is not stringent, in that the microwave energy absorbed by the prostate is only a small fraction of the total energy applied by thermotherapy machines. 16 It was hypothesized quite early that the clinical benefit of HE-TUMT might be related to the achieved intraprostatic temperatures and the duration of heat exposure. 16 Actually, thermal damage generally follows an exponential temperature/time relationship known as the Arrhenius model 12 ; 45°C has been shown to be the minimum threshold for coagulation necrosis of prostatic stromal and epithelial tissue in a heat exposure time not exceeding 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,9 Furthermore, "treatment energy," which is commonly used to describe the intensity of TUMT, is not stringent, in that the microwave energy absorbed by the prostate is only a small fraction of the total energy applied by thermotherapy machines. 16 It was hypothesized quite early that the clinical benefit of HE-TUMT might be related to the achieved intraprostatic temperatures and the duration of heat exposure. 16 Actually, thermal damage generally follows an exponential temperature/time relationship known as the Arrhenius model 12 ; 45°C has been shown to be the minimum threshold for coagulation necrosis of prostatic stromal and epithelial tissue in a heat exposure time not exceeding 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…16 It was hypothesized quite early that the clinical benefit of HE-TUMT might be related to the achieved intraprostatic temperatures and the duration of heat exposure. 16 Actually, thermal damage generally follows an exponential temperature/time relationship known as the Arrhenius model 12 ; 45°C has been shown to be the minimum threshold for coagulation necrosis of prostatic stromal and epithelial tissue in a heat exposure time not exceeding 60 minutes. 17 As shown in Tables 3 and 4, symptomatic and flow-rate responders did not reach high temperatures (i.e., Ͼ45°C) for longer times than poor responders.…”
Section: Discussionmentioning
confidence: 99%
“…These``intrinsic'' factors include histologic composition and vasculature of the prostate. Especially, the intraprostatic blood ow is expected to in¯uence signi®cantly the temperature achieved during treatment due to the amount of thermal energy absorbed by the circulating blood (heat-sink phenomenon) [9,19]. d' Ancona et al, [20] analyzed biopsy material by quantitative light microscopy techniques, and found a clear trend toward a lower microvessel density among good responders.…”
Section: Discussionmentioning
confidence: 99%
“…Con-cerning intrinsic prostate factors that determine the heat±tissue interactions, prostatic blood perfusion is an important regulatory parameter of the temperature achieved during treatment [9]. High-blood perfusion of the prostate results in lowering of the core temperature during the treatment, thus diminishing the therapeutic effect (heat-sink phenomenon).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods that help control this parameter are being investigated, including interstitial thermosensors, magnetic resonance thermometry, radiometric microwave methods, and ultrasound thermography. Besides treatment parameters, the increase in temperature is strongly correlated to the vascularization of the prostate and the cooling effect of prostatic blood flow (heat-sink phenomenon) [39]. Djavan et al [40] found that clinical outcome is more favorable in cases of high PSA, which is explained by the higher thermosensibility of epithelium than stroma.…”
Section: Transurethral Microwave Thermotherapy (Tumt)mentioning
confidence: 99%